Emptiness formation probability for the spin-1/2 XX chain with three spin and uniform long-range interactions - Lou, P.; Lee, J.Y. (Condensed Matter Physics, 2007)
The emptiness formation probability (EFP) that the first n spins of the chain are all aligned downwards is studied for the one-dimensional spin- 1/2 XX chain system with both critical and non-critical regimes with three spin and uniform long-range interactions. By using the emptiness formation probability P(n), the block-block entanglement Sn and the magnetization Mz, the properties of the system are also studied. It is worthy of note
that when the quantum phase transition from the phase III to the phase II occurs, the Emptiness Formation Probability P(n) of the system decreases, but the block-block entanglement Sn increases. Дослiджується ймовiрнiсть формування порожнини, тобто ймовiрнiсть того, що n перших спiнiв у ланцюжку є спрямованi вниз, для одновимiрної спiн- 1/2 XX ланцюжкової системи з триспiновою i однорiдною далекосяжною взаємодiями як у критичному, так i у некритичному режимах. З використанням ймовiрностi формування порожнини P(n), блок-блок сплутаностi Sn i намагнiченостi Mz дослiджуються також властивостi такої спiнової системи. Важливо вiдзначити, що коли вiдбувається квантовий фазовий перехiд з фази III у фазу II, ймовiрнiсть формування порожнини системи P(n) зменшується, тодi як блок-блок сплутанiсть Sn зростає.